P475 Review of the management of bilious vomiting in term neonates and identify differences in management outside working hours in CUMH. (June 2019) - Stephens, Carol; o'connell, liam
Abstract : Bilious vomiting is a common reason for admission to the neonatal unit. In the majority, the episode is benign. In a small minority, there is serious underlying pathology which is time critical. Identification and differentiation between these entities is crucial but challenging. Management is variable amongst centres and often case specific and certainly always time critical. When a pathological cause is suspected, occasionally it is warranted to transfer the sick neonate to a surgical unit without the delay of local investigations. Methods: This was a retrospective review in CUMH over seven years. Inclusion criteria were all infants admitted directly to the unit with bilious vomiting. Exclusion criteria included infants who were admitted for a different primary concern including premature infants. Admission Logbook of unit identified infants, online reporting systems were used to review discharge summaries. Online laboratory and radiology database were accessed. Results: 213 infants were included. Management varied throughout the years. Earlier, most infants had a PFA, Septic Work Up (SWU) and contrast study in contrast to the latter years where most had a PFA and a SWU. We postulate in the latter years there was a lower threshold for admission on the background of a neonatal death and subsequently more infants were conservatively managed and observed in the unit. 22% had contrast studies out of hours, 18% were subsequently transferred to a surgical unit in light of a positive finding. Positive findings included microcolon, volvulus, Hirschprungs and obstruction. The majority of infants were discharged with no complications. Discussion: Bilious vomiting is synonymous with intestinal obstruction and should be considered this until proven otherwise . Management is time critical given the potential consequences of a volvulus and the ischaemic threat to the bowel with the window of opportunity being approximately six hours (3) A national guideline is now warranted.